1987
DOI: 10.1042/bj2480085
|View full text |Cite
|
Sign up to set email alerts
|

Constant and variable domains of different disaccharide structure in corneal keratan sulphate chains

Abstract: Four peptidokeratan sulphate fractions of different Mr and degree of sulphation were cut from the pig corneal keratan sulphate distribution spectrum. After exhaustive digestion with keratanase, the fragments were separated on DEAE-Sephacel and Bio-Gel P-10 and analysed for their Mr, degree of sulphation and amino sugar and neutral sugar content. It was found that every glycosaminoglycan chain is constructed of a constant domain of non-sulphated and monosulphated disaccharide units and a variable domain of disu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
48
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 18 publications
4
48
0
Order By: Relevance
“…1, panel B) suggests that a critical minimum polymer size is necessary for synthesis of oversulfated regions in the chain interior. Conversely, as suggested by earlier in vitro studies (44,45), keratan sulfate chain elongation may only proceed in conjunction with efficient sulfation, and the undersulfated chains in both types of MCD, and in both tissues examined, were significantly shorter than those isolated from normal tissues. Thus, premature chain termination in the absence of appropriate sulfation may occur if sulfation The migrations of disaccharide glcNAc␤1, 3gal, the trisaccharide gal␤1,4glcNAc ␤1,3gal, and neuA were determined by coelectrophoresis of standards as reported (29) (data not shown).…”
Section: Discussionmentioning
confidence: 55%
“…1, panel B) suggests that a critical minimum polymer size is necessary for synthesis of oversulfated regions in the chain interior. Conversely, as suggested by earlier in vitro studies (44,45), keratan sulfate chain elongation may only proceed in conjunction with efficient sulfation, and the undersulfated chains in both types of MCD, and in both tissues examined, were significantly shorter than those isolated from normal tissues. Thus, premature chain termination in the absence of appropriate sulfation may occur if sulfation The migrations of disaccharide glcNAc␤1, 3gal, the trisaccharide gal␤1,4glcNAc ␤1,3gal, and neuA were determined by coelectrophoresis of standards as reported (29) (data not shown).…”
Section: Discussionmentioning
confidence: 55%
“…Also, although information about the levels of galactose sulphation at the chain cap is available none is available about the levels along the repeat region. However, previous work has reported decreasing levels of galactose sulphation along the repeat region towards the reducing terminus (the protein core) (Lauder et al, 1994;Oeben et a]., 1987).…”
Section: Discussionmentioning
confidence: 87%
“…The 0-linked keratan sulphate chains from bovine nasal septum are also short, having a repeat region of about seven to nine disaccharides (Stuhlstatz et al, 1989). However, Oeben et al (1987) found Nlinked keratan sulphate chains from pig cornea with repeat regions of 10-52 disaccharides. These workers found no N-acetylneuraminic acid chain caps so the chains may be even longer in vivo.…”
Section: Discussionmentioning
confidence: 97%
“…This is identical structure to that we found. Oeben et al (40), however, reported a biantennary complex type structure that has a sialylgalactosyl N-acetyllactosamine and e), pcDNA3-hCGn6ST (lanes b and f), pcDNA3-hKSG6ST (lanes c and g), and both pcDNA3-hCGn6ST and pcDNA3-hKSG6ST vectors (lanes d and h). Membrane protein fractions were prepared from those transfectants and separated by SDS-PAGE followed by Coomassie Blue staining (lanes a-d) or Western blotting using an anti-keratan sulfate antibody, 5D4 (lanes e-h).…”
Section: Discussionmentioning
confidence: 97%